Aromatic Thioethers as Novel Luminophores with Aggregation‐Induced Fluorescence and Phosphorescence. Issue 55 (9th August 2017) - Riebe, Steffen; Vallet, Cecilia; van der Vight, Felix; Gonzalez‐Abradelo, Dario; Wölper, Christoph; Strassert, Cristian A.; Jansen, Georg; Knauer, Shirley; Voskuhl, Jens
Abstract: Here we report on a novel system based on aromatic thioethers with unique luminescence properties. Fifteen different compounds were investigated in detail on their luminescence properties using UV/Vis absorption and steady‐state and time‐resolved luminescence spectroscopy. Excited state lifetimes as well as quantum yields were determined, and the toxicity towards HeLa cells was investigated. Besides X‐ray analyses also quantum chemical calculations were performed to gain deeper insights in the unique behavior of this facile system. The studied compounds reveal remarkable fluorescence emission ranging from 437 to 588 nm as well as phosphorescence (up to 5 μs). Abstract : Sulfur does the trick : A novel class of luminophores with aggregation‐induced fluorescence and phosphorescence properties is described. The aromatic thioethers stack in poor solvents, which lead to an emission due to a restriction of intramolecular rotation (RIR). The aggregates formed were investigated concerning their photophysical properties, morphology and possible use in biological imaging.